THE EFFECT OF APPLYING THE PROJECT BASED LEARNING MODEL AGAINST STUDENT LEARNING OUTCOMES - Ilyas Ilyas; Ulil Azmi; Safrijal Safrijal (International Journal of Social Science, 2023)
Project Based Learning is a learning model or approach that provides opportunities for teachers to manage learning in the classroom by involving project work. Ministry of Education and Culture (2015: 46) argues thatProject Based Learningis a learning model that involves students in an activity (project) that produces a product.Project Based Learningis a learning model that uses problems as a first step in gathering and integrating new knowledge based on experience in real activities. The approach used in this study is a quantitative approach which can be interpreted as a research method based on the philosophy of positivism, used to examine certain populations or samples, sampling techniques are generally carried out randomly, data collection uses research instruments, data analysis is quantitative or statistical with the aim of testing the hypotheses that have been set. Based on the results of the analysis of research data and discussion in this study, it can be concluded that there is an influence of the modelProject Based Learning on cube material on student learning outcomes of the physics education study program, the teaching and education faculty of Jabal Ghafur University. The existence of a significant influence is indicated by a probability number of 0.000 with a significance level of 0.01. This means that there is a significant influence on learning outcomes after applying the modelProject Based Learning